2021
DOI: 10.3389/fpsyg.2021.747039
|View full text |Cite
|
Sign up to set email alerts
|

Reading Struggle Stories of Role Models Can Improve Students' Growth Mindsets

Abstract: Previous studies have suggested that reading stories of role models can improve the growth mindsets of students. The current study aimed to investigate the types of stories that can increase the growth mindsets of high school students, undergraduates, and graduates and how many specific stories undergraduates with low and high perseverance need to read to improve their growth mindsets. In study 1, high school students, undergraduates, and graduates were assigned to read either five struggle stories or five ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Therefore, medical institutions, nursing organizations, and nursing managers should realize the key role of implicit theories in nurses’ coping with stress or challenges, and create a work atmosphere that emphasizes that efforts can change the status quo and achieve success. For those nurses with entity theory, nursing managers should encourage them to be proactive, using peer support ( Sheffler and Cheung, 2020 ) and role model learning ( Du et al, 2021 ) to promote their incremental theory. In addition, cultivating nurses’ willpower, the meaning of life, and other positive psychological qualities is also conducive to promoting nurses’ adversity adaptability.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, medical institutions, nursing organizations, and nursing managers should realize the key role of implicit theories in nurses’ coping with stress or challenges, and create a work atmosphere that emphasizes that efforts can change the status quo and achieve success. For those nurses with entity theory, nursing managers should encourage them to be proactive, using peer support ( Sheffler and Cheung, 2020 ) and role model learning ( Du et al, 2021 ) to promote their incremental theory. In addition, cultivating nurses’ willpower, the meaning of life, and other positive psychological qualities is also conducive to promoting nurses’ adversity adaptability.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Du et al, ( 2021b ) focused on how many struggle stories undergraduates with low and high levels of perseverance need to read to improve their growth mindsets. They found that the growth mindsets of undergraduates with a low level of perseverance increased after reading 2 struggle stories of role models and increased further after reading 5 struggle stories of role models.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the growth mindsets of undergraduates with a low level of perseverance increased after reading 2 struggle stories of role models and increased further after reading 5 struggle stories of role models. More importantly, the level of growth mindset of undergraduates with a low level of perseverance was equal to that of undergraduates with a high level of perseverance after reading 5 struggle stories of role models (Du et al, 2021b ). However, the participants in Du et al, ( 2021b ) did not experience failure before reading the stories.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations